Mindfulness, social evaluation anxiety, and self-regulation: exploring their association on impulsive behavior among athletes - Zhong, Zhangyi; Jiang, Hongyu; Wang, Huilin; Liu, Yang (Frontiers in Psychiatry, 2024)
Introduction Athletes, due to frequent physical interactions in competitive sports, are prone to impulsive behavior. Impulsive behavior is a prevalent psychological factor in sports, often leading to performance-affecting errors. This cross-sectional survey investigated the relationship between mindfulness and athletes’ impulsive behavior. Methods We sampled 403 athletes from youth training centers, universities, sports academies, and clubs in China using convenience and snowball sampling. Using AMOS v23, we analyzed the data with a structural equation model. Results Our structural equation model confirmed that mindfulness and self-regulation inversely correlate with impulsive behavior, while social evaluation anxiety positively correlates with impulsive behavior. Furthermore, self-regulation and social evaluation anxiety serve as intermediaries in the link between mindfulness and impulsive behavior. Discussions This research suggests introducing mindfulness meditation practices in competitive settings to improve athletes’ social evaluation anxiety and enhance their self-regulation abilities, thereby boosting their psychological health and curbing impulsive behavior.